Formulary Drug Review: Sufentanil Sublingual - Baker, Danial E. (Hosp Pharm, 2019)
Each month, subscribers to The Formulary Monograph Service receive 5 to 6 well-documented monographs on drugs that are newly released or are in late phase 3 trials. The monographs are targeted to Pharmacy & Therapeutics Committees. Subscribers also receive monthly 1-page summary monographs on agents that are useful for agendas and pharmacy/nursing in-services. A comprehensive target drug utilization evaluation/medication use evaluation (DUE/MUE) is also provided each month. With a subscription, the monographs are available online to subscribers. Monographs can be customized to meet the needs of a facility. Through the cooperation of The Formulary, Hospital Pharmacy publishes selected reviews in this column. For more information about The Formulary Monograph Service, contact Wolters Kluwer customer service at 866-397-3433.